Ecology and Economic Study of Leaf Litter as Organic Fertilizer in Reclamation Land Used on Lime - Nurtjahyani, Supiana Dian; Oktavitria, Dwi; Wulan, Sri; Maulidina, Nova; Cintamulya, Imas; Purnomo, Eko (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 1 (2020): ATBES, 2020)
The success of reclamation is largely determined by many things including the fertility of the planting media. The fertility of the planting media is related to fertilizer, from the litter found in post-mining land that can be utilized for making organic fertilizer. The purpose of this study is to examine the ecological and economic aspects of leaf litter as organic fertilizer in the reclaimed land of limestone mining. Method: Laboratory experimental research with method Bokhasi Results from this study proved that there are differences in the nutrient content of P, C and N in the reclamation land in 2010, 2014 and 2016. Processing leaf litter into organic fertilizer can provide ecological and economic benefits for the company and for the surrounding community.